Echocardiographic evaluation of left ventricular mechanics in sarcoidosis patients without overt heart disease: a systematic review and meta-analysis - Sonaglioni, Andrea; Fagiani, Valeria; Rigoni, Marta; Nicolosi, Gian Luigi; Lucidi, Alessandro; Caminati, Antonella; Lombardo, Michele; Harari, Sergio (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: During the last decade, a small number of studies have used speckle tracking echocardiography (STE) to investigate sarcoidosis effect on left ventricular (LV) mechanics in patients without overt heart disease. The present systematic review and meta-analysis has been primarily designed to summarize the main findings of these studies and to examine the overall influence of sarcoidosis on LV-global longitudinal strain (GLS) and left ventricular ejection fraction (LVEF). Methods: All echocardiographic studies assessing conventional echoDoppler parameters and myocardial strain indices in patients with extracardiac sarcoidosis (ECS) vs. healthy controls, selected from PubMed and EMBASE databases, were included. The risk of bias was assessed by using the National Institutes of Health (NIH) Quality Assessment of Case-Control Studies. Continuous data (LV-GLS and LVEF) were pooled as a standardized mean difference (SMD) comparing sarcoidosis group with healthy controls. The overall SMDs of LV-GLS and LVEF were calculated using the random-effect model. Results: The full-text of 13 studies with 785 ECS patients and 567 healthy controls were analyzed. Both average LVEF (60.5±6.6 vs 63.0±4.8%, P